Relationship of Circulating Mirnas With Insulin Resistance and Metabolic Dysfunction in Adolescents - Payolla, Tanyara (Curr Dev Nutr, 2021)
OBJECTIVES: To evaluate the relationship of plasma expression of miR-122, -375, -139, 15-a and -let7c with insulin resistance and factors related to metabolic syndrome (MetS) in adolescents. METHODS: Data from 188 adolescents aged 12–19 years participating in a cross-sectional population-based study were analyzed, all non-smokers, without acute inflammatory diseases and cancer, and without the use of medication that would interfere in the outcome. The quantification of circulating miRNA was performed by RT-PCR, using the Fluidigm chip technique. The miRNA expression was compared among adolescents grouped by the absence (n = 94) or presence of insulin resistance (n = 94)—categorized according to with the HOMA-IR index -, and the absence (n = 92) or presence of 1 (n = 59), 2 (n = 23), 3 (n = 10) or 4 (n = 4) factors related to MetS. The comparison of means was performed using the Mann-Whitney test for two samples or Kruskal-Wallis followed by Dunn's post-test to compare three or more samples. RESULTS: Insulin resistance was identified in 50% of the individuals (HOMA-IR > 2.7). In adolescents with insulin resistance, the plasma expression of miR-122 was higher in comparison to normoglycemic individuals and was positively associated with fasting insulinemia (r = 0.157; P = 0.031), HOMA-IR index (r = 0.160; P = 0.028) and plasma hepcidin (r = 0.209; P = 0.005) levels. When evaluating the expression according to the number of factors related to MetS, the expression of miR-let7c, -139 and -15a increased according to the increase of the factors related to MetS. The opposite effect was observed in relation to miR-375. Individuals with 3 or more factors differed from groups whith 1 or 2 factores for plasma miR-375, -139, 15-a and -let7c expression. MiR-375 showed a negative association with body weight (r = −0.169; P = 0.019), while miR-139 was associated with systolic (r = 0.153; P = 0.055) and diastolic (r = 0.193; P = 0.016) blood pressure. Plasma miR-15a expression had a positive correlation with diastolic blood pressure (r = 0.198; P = 0.0064). MiR-let7c showed a positive correlation plasma TG (r = 0.156; P = 0.029). CONCLUSIONS: Plasma miR 122 expression was related to insulin resistance, while plasma miR 375, 139, 15 a and let7c expressions were associated with MetS in adolescents. FUNDING SOURCES: From Sao Paulo Research Foundation and National Council for Scientific and Technological Development